An Axiomatic Approach to the General Theory of Compounds - Stroński, Krzysztof; Machowski, Szymon (Lingua Posnaniensis, 2012)
The aim of this article is to provide a logical reconstruction of the general theory of compounding. The theory formulated here is partly based on the axiomatic approach to general morphology presented in Bańczerowski (1997) and it can be conceived of as its continuation. As a point of departure for the present investigation a set of primitive terms is constructed and axioms formulated, followed by basic definitions and theorems. T hen the authors introduce discrete dimensions making it possible to describe morphological, syntactic and semantic properties of compound words. The analyses of the dimensions lead to various structural classifications of the compound words.